Prevalence of psychosocial problems in adolescents of central India: a descriptive cross sectional study - Nimje, Ashish T.; Gawande, Avinash V.; Narlawar, Uday W. (International Journal Of Community Medicine And Public Health, 2023)
Background: Adolescent’s psychosocial disorders exhibit as iceberg phenomenon and are one of the hidden health problems in population. Adolescents suffer from psychosocial problems at one or the other time during their development. Aim of study was to study the prevalence of psychosocial problems among adolescent. Methods: A community based descriptive cross-sectional study was conducted in urban field practice area of govt. medical college, Nagpur in Maharashtra. House to house survey was conducted and face to face interview was taken among 330 adolescents out of which 214 (64.84%) were male and 116 (35.16%) were female. Peadiatric Symptom Checklist Youth version (PSC-Y) was used as a tool to study the psychosocial problem. Results: In present study, overall prevalence of psychosocial problem was found to be 33.03%. Prevalence of psychosocial problem in male and female was 34.11% and 31.03% respectively. Psychosocial problems were more in age group of 14-16 years (39.69%) followed by 10-13 years 34 (31.48%) and 17-19 years age group 23 (25.27%). Conclusions: On basis of findings using PSC-Y, it is concluded that, a sizeable population (about one third of the adolescents) were suffered from psychosocial problem and the attention problem was most commonly found using PSC-Y subscales.